Antibody Production in Murine Polymicrobial Sepsis—Kinetics and Key Players - Nicolai, Oliver; Pötschke, Christian; Schmoeckel, Katrin; Darisipudi, Murthy N.; van der Linde, Julia; Raafat, Dina; Bröker, Barbara M. (Frontiers in Immunology, 2020)
Although antigen-specific priming of antibody responses is impaired during sepsis, there is nevertheless a strong increase in IgM and IgG serum concentrations. Using colon ascendens stent peritonitis (CASP), a mouse model of polymicrobial abdominal sepsis, we observed substantial increases in IgM as well as IgG of all subclasses, starting at day three and peaking two weeks after sepsis induction. The dominant source of antibody-secreting cells was by far the spleen, with a minor contribution of the mesenteric lymph nodes. Remarkably, sepsis induction in splenectomized mice did not change the dynamics of the serum IgM/IgG reaction, indicating that the marginal zone B cells, which almost exclusively reside in the spleen, are dispensable in such a setting. Hence, in systemic bacterial infection, the function of the spleen as dominant niche of antibody-producing cells can be compensated by extra-splenic B cell populations as well as other lymphoid organs. Depletion of CD4+ T cells did not affect the IgM response, while it impaired IgG generation of all subclasses with the exception of IgG3. Taken together, our data demonstrate that the robust class-switched antibody response in sepsis encompasses both T cell-dependent and -independent components.